2023
DOI: 10.1177/21582440231187612
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and Preferences of Senior High School Students About Written Corrective Feedback in Pakistan

Abstract: Written corrective feedback (WCF) in enhancing writing proficiency has been the subject of numerous studies, but few studies have examined students’ perceptions about the value of feedback on their written errors. Language teachers use global tools and techniques to give students feedback on their written work. How feedback is delivered and received by students is valued differently. The current study concentrated on how students interpret written corrective feedback and which WCF tactics they favor in writing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
0
0
0
Order By: Relevance
“…Students learn their skills and weaknesses as writers by reading what their teachers have written about them. Moreover, similar results also happened in Putra (2022) and Rasool et al (2023), who found that students experience demotivation and a sense of despair when confronted with intricate feedback conveyed through loops, underlining, and a lack of corrections and constructive input by the teacher. The preferred approach among students invariably centres on instructional techniques that involve clear explanations.…”
Section: 2%supporting
confidence: 68%
“…Students learn their skills and weaknesses as writers by reading what their teachers have written about them. Moreover, similar results also happened in Putra (2022) and Rasool et al (2023), who found that students experience demotivation and a sense of despair when confronted with intricate feedback conveyed through loops, underlining, and a lack of corrections and constructive input by the teacher. The preferred approach among students invariably centres on instructional techniques that involve clear explanations.…”
Section: 2%supporting
confidence: 68%